Sphingosine 1 phosphate promotes hypertension specific memory T cell trafficking in response to repeated hypertensive challenges - Itani, Maha M.; Jarrah, Hala; Maaliki, Dina; Radwan, Zeina; Farhat, Rima; Itani, Hana A. (Frontiers in Physiology, 2022)
We have previously shown that effector memory (TEM) cells accumulate in the bone marrow (BM) and the kidney in response to L-NAME/high salt challenge. It is not well understood if measures to block the exodus of TEM cells prevent redistribution of these cells and protect from hypertension-induced renal damage. We hypothesized that TEM cells that accumulate in the BM respond to repeated salt challenges and can be reactivated and circulate to the kidney. Thus, to determine if mobilization of BM TEM cells and secondary lymphoid organs contribute to the hypertensive response to delayed salt challenges, we employed fingolimod (FTY720), an S1PR1 functional antagonist by downregulating S1PR, which inhibits the egress of TEM cells used effectively in the treatment of multiple sclerosis and cardiovascular diseases. We exposed WT mice to the L-NAME for 2 weeks, followed by a wash-out period, a high salt diet feeding for 4 weeks, a wash-out period, and then a second high salt challenge with or without fingolimod. A striking finding is that TEM cell egress was dramatically attenuated from the BM of mice treated with fingolimod with an associated reduction of renal TEM cells. Mice receiving fingolimod were protected from hypertension. We found that WT mice that received fingolimod during the second high salt challenge had a marked decrease in the renal damage markers. CD3+ T cell infiltration was significantly attenuated in the fingolimod treated mice. To further examine the redistribution of BM TEM cells in response to repeated hypertensive stimuli, we harvested the bone marrow from CD45.2 mice following the repeated high salt protocol with or without fingolimod; TEM cells were sorted and adoptively transferred (AT) to CD45.1 naïve recipients. AT TEM cells from mice treated with fingolimod failed to home to the BM and traffic to the kidney in response to a high salt diet. We conclude that memory T cell mobilization contributes to the predisposition to hypertension and end-organ damage for prolonged periods following an initial episode of hypertension. Blocking the exodus of reactivated TEM cells from the BM protects the kidney from hypertension-induced end-organ damage.